A Assistance with the Yaumi Practice Program at the Salimah Ta'lim Council in Padang Pariaman Regency: Assistance with the Yaumi Practice Program - azmiyah azhari; Martin Kustati; Gusmirawati (Sekolah Tinggi Agama Islam Barumun Raya (STAI BR) Sibuhuan, 2023)
The yaumi practices referred to in this assistance are sunnah practices or worship which should be done consistently every day in any situation and condition, in the form of tahajud worship, sunnah fasting Monday-Thursday, and recitations of the Qur'an. As technology advances, to make it easier for the congregation of the ta'lim assembly to report the worship they have carried out, formats and signs have been created to indicate whether they have carried out the predetermined yaumi practice, whether they have achieved the agreed target or not. This assistance aims to illustrate the interest and commitment of the Salimah Ta'lim Council congregation in the district. Nan Sabaris Padang Pariaman Regency in carrying out sunnah worship, especially the tahajud sunnah prayer, sunnah fasting Monday-Thursday, and reciting the Qur'an via WhatsApp media. This mentoring program uses the Asset Based Community Development (ABCD) method through observation, interviews, and data collection. The results of the mentoring show a change in attitude, istiqomahan, and quantity of congregational worship in carrying out tahajjud worship, Monday-Thursday fasting, recitations, which were initially feels hard to carry out. Because we are always motivated and reminded at every meeting and light discussion via WhatsApp, over time it becomes a habit, so that the congregation is motivated to carry out sunnah worship sincerely without any coercion, and with their own initiative to report their worship. This routine of performing sunnah prayers becomes spiritual energy that influences the morals and manners of the congregation of the Salimah Ta'lim Council.